UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA MELALUI DISKUSI KELOMPOK BERBANTUAN ALAT PERAGA - Yanti, Sri (Universitas Tanjungpura, 2019)
AbstractThe group discussion is the activity of a group of students, speaking exchanging information and opinions on a topic, where each student wants to find answers to all the possibilities. This study aims to find out and analyze the improvement of understanding the concept of mathematics students of class IX A SMP Negeri 21 Pontianak after the learning of mathematics through discussion groups assisted props. This study is a classroom action research consisting of two cycles, with the help of teacher and student activity observation sheets, student activity sheets for group discussion and test result of learning. Based on the results of data analysis, there is an increased understanding of mathematical concepts of students Through the implementation of teaching-assisted group discussion of learning aids occur increased student activity in learning. An increase in the percentage of student activity from cycles I and cycle II by 18%. Through the implementation of learning group-assisted discussion of visual aids, there was an increase in the understanding of mathematical concepts of students from cycle I and cycle II seen from the results of concept comprehension tests provided, there was an average score increase of 9.45 and a 22.85% increase in the percentage of mastery.Â Keywords: Conceptual Understanding, Group Discussion, Props